CCCDTD5: Reducing the risk of later‐life dementia. Evidence informing the Fifth Canadian Consensus Conference on the Diagnosis and Treatment of Dementia (CCCDTD‐5). Issue 1 (11th November 2020) - Rockwood, Kenneth; Andrew, Melissa K.; Aubertin‐Leheudre, Mylène; Belleville, Sylvie; Bherer, Louis; Bowles, Susan K.; Kehler, D Scott; Lim, Andrew; Middleton, Laura; Phillips, Natalie; Wallace, Lindsay M.K.
Abstract: The Fifth Canadian Consensus Conference on the Diagnosis and Treatment of Dementia (CCCDTD‐5) was a year‐long process to synthesize the best available evidence on several topics. Our group undertook evaluation of risk reduction, in eight domains: nutrition; physical activity; hearing; sleep; cognitive training and stimulation; social engagement and education; frailty; and medications. Here we describe the rationale for the undertaking and summarize the background evidence—this is also tabulated in the Appendix. We further comment specifically on the relationship between age and dementia, and offer some suggestions for how reducing the risk of dementia in the seventh decade and beyond might be considered if we are to improve prospects for prevention in the near term. We draw to attention that a well‐specified model of success in dementia prevention need not equate to the elimination of cognitive impairment in late life.